2021
DOI: 10.3389/fimmu.2021.651687
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Indoleamine 2,3-Dioxygenase in Acute Myeloid Leukemia: A Systematic Review

Abstract: Background: The immunomodulatory enzyme, indoleamine 2,3-dioxygenase (IDO) facilitates tryptophan catabolism at the rate-limiting step of the kynurenine (Kyn) pathway. IDO expression and elevations in Kyn metabolites are associated with immunosuppressive tumor microenvironment including T cell proliferative arrest and generation of regulatory T cells (Tregs) which can favor tumor progression. However, the extent of the role of IDO in acute myeloid leukemia (AML) is currently ill-defined. This study reviews the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Given that Kyn has been recognized as an immunosuppressive factor 14 , 15 , the above results prompted us to assume that the increased circulating Kyn could be a compensatory effect against chronic inflammation in individuals with obesity. We thus injected the mice subcutaneously with Kyn (20 mg kg −1 d −1 ) or PBS for 30 consecutive days starting from the eighth weeks of a 12-week period of HFD challenge.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that Kyn has been recognized as an immunosuppressive factor 14 , 15 , the above results prompted us to assume that the increased circulating Kyn could be a compensatory effect against chronic inflammation in individuals with obesity. We thus injected the mice subcutaneously with Kyn (20 mg kg −1 d −1 ) or PBS for 30 consecutive days starting from the eighth weeks of a 12-week period of HFD challenge.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpressed IDO1 exhausts circulating Trp and competitively inhibits the production of other Trp metabolites such as serotonin, which involves in satiety generation and appetite suppression 12 , 13 . Kyn is generally recognized as an immunosuppressive factor 14 , 15 , while obesity is always accompanied by the low-grade chronic inflammation. Therefore, the increase of circulating Kyn has been considered as a compensatory effect 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…In AML and myelodysplastic syndromes, IDO1 expression has been identified as an independent adverse prognostic factor [ 111 ], able to impair immune response by Treg induction [ 140 ]. Using IDO1 inhibitor is promising in AML [ 141 ] and may be interesting in pDC-AML. T-cells from the AML BM microenvironment also express several immune checkpoint molecules such as PD1, CTLA-4, LAG3, TIM3, GITR, OX40, 4-1BB and ICOS, whereas AML blasts express 4-1BBL, CD80, CD86, ICOSL, PD-L1, PD-L2 and OX40L.…”
Section: Current Therapies and Perspective In Pdc-amlmentioning
confidence: 99%
“…Importantly, repopulating tumor cells can escape immune surveillance by transferring to adjacent CD8+ T cells the KYN metabolite, which in turn activates the aryl hydrocarbon receptor (AhR) and increases PD-1 expression [129]. The expression levels of IDO1 and KYN and the activity of KP have also been investigated in the context of hematological malignancies, in particular in AML, where an extensive review of the literature has been recently performed [130,131]. Briefly, an initial study found that the KYN/Trp ratio was higher in the serum of AML patients compared to healthy controls, suggesting that increased IDO activity is associated with lower survival [132].…”
Section: Emerging Roles Of Tryptophan Metabolismmentioning
confidence: 99%